Caracterização hidrogeoquímica e isotópica (87Sr/86Sr) dos sistemas aquíferos Barreiras e Pirabas Superior nos municípios de Castanhal e Santa Maria do Pará, Estado do Pará - SILVA, Igor Rafael Furtado da (Universidade Federal do Pará, 2019)
Geological surveys and remote sensing investigations in northeastern Pará State identified features and tectonic structures that characterized the neotectonic process in this region. Hydrogeological investigations in the Metropolitan Region of Belém and its surroundings were also held with the objective of characterizing the waters of the Barreiras and Pirabas (Lower Pirabas and Upper Pirabas) systems, and to evaluate the possibility of a mix between these aquifers through faults and fractures systems and the degree of their vulnerability in relation to anthropogenic inputs. Alongside the hydrogeochemical investigations, studies using isotopic signature of strontium (87Sr/86Sr) in groundwater have been performed in order to characterize the Sr sources for each aquifer system, their geochemical histories and the potential water mixture between them. Thus, studies were carried out in the isotopic composition of strontium (87Sr/86Sr) and hydrogeochemical analyzes in subareas from Castanhal and Santa Maria do Pará, aimed at the characterization of these aquifer systems, as well as detection of any possible case mixtures occur among them. The hydrogeochemical results revealed distinct features between aquifer systems studied, highlighting the parameters pH (3.52 to 5.97 in Barreiras System; 6.17 to 6.60 in Upper Pirabas System), Electrical Conductivity (45.50 to 193.90 S/cm in Barreiras; 133.80 to 194.70 S/cm in Upper Pirabas), HCO3– (up to 32.88 mg/L Barreiras; 89.10 to 117.15 mg/L in Upper Pirabas System), Cl– (3.87 to 40.50 mg/L Barreiras; 3.33 to 6.32 mg/L in Upper Pirabas), Na+ (1.00 to 18.55 mg/L in Barreiras System; 1.35 to 2.55 mg/L Pirabas Upper System), Mg2+ (up to 1.26 mg/L Barreiras, from 2.03 to 2.81 mg/L in Upper Pirabas), Ca2+ (up to 5, 14 mg/L in Barreiras, from 21.30 to 27.38 mg/L in Upper Pirabas) and Sr2+ (0.0065 to 0.0874 mg/L in Barreiras; 0.2129 to 0.2679 mg/L in Upper Pirabas). Statistical studies have shown good correlations between the aquifers (≥ 0.7), especially during the rainy season. According to the analyzes of Piper diagrams it was found that the Barreiras aquifer has predominantly Cl–-Na+ waters, which are influenced by the contribution of meteoric water and the anthropogenic action, with pH values acids around 4.7 and high vulnerability. The waters of the Upper Pirabas Aquifer System are mostly HCO3–-Ca2+, being this hydrochemical facies strongly influenced by the dissolution of carbonate, having a pH higher than 6 and less vulnerability to human action. Isotopic results showed that the Barreiras Aquifer samples are more radiogenic (0.712716 to 0.723881) that the sample of the Upper Pirabas Aquifer System (0.706080 to 0.709063) during the dry season. During the rainy season occurred the homogenization process of isotopic ratios of aquifer systems under study. Samples of the Barreiras Aquifer System there was significant decrease in values of isotopic the 87Sr/86Sr ratios from 0.712716 to 0.723881 for a range from 0.704239 to 0.709957, getting these values similar to those found in the waters of the Upper Pirabas Aquifer System. Composition diagrams of the major ions against chloride varied greatly, possibly indicating the presence of more than two end members in these waters mixing process. The multivariate statistical analysis (PCA), together with the diagram 1/Sr vs. 87Sr/86Sr showed a trend mixture between these aquifers and the meteoric waters during the rainy season. The hydrogeochemical modeling (Schoeller diagram) indicated that the degree of mixing between of the waters of the Upper Aquifer Pirabas and Barreiras is around 10% during the rainy season. Isotopic and hydrochemical studies together with on the existing neotectonic structure in the Metropolitan Region of Belém and its surroundings suggest mixing processes between Barreiras and Upper Pirabas aquifers systems, mainly in the rainy period. The lack of a planning and management system of the use of groundwater sources in the Castanhal and Santa Maria do Pará towns, as well as throughout the Metropolitan Region of Belém, alert to the risk of contamination of the Upper Pirabas Aquifer System by anthropogenic action, which represent the best alternative for public supply of the population of Belém and its surroundings with a excellent water quality with regard to portability for human consumption.